Pengaruh Keadilan, Sistem Perpajakan, Diskriminasi, Kemungkinan Terdeteksi Kecurangan Terhadap Persepsi WPOP Mengenai Etika Penggelapan Pajak - Aprilia Agustinus Paskarely; Kenny Ardillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The purpose of this research to analyze the effect of tax justice, taxation system, discrimination, the possibility of fraud on the perception of taxpayers regarding the ethics of individual taxpayers' tax evasion scattered in the Bekasi Madya Tax Service Office. This study uses a quantitative method. The number of samples used in this study were 100 respondents. The sampling technique used is purposive sampling using the Slovin formula. Data collection using a questionnaire and processed using SPSS statistics version 25. The analysis technique used is multiple linear regression. The results of the study show that fairness and the possibility of detecting fraud have a negative effect on taxpayers' perceptions of tax evasion ethics, while the taxation system and discrimination have no significant effect on taxpayers' perceptions of tax evasion ethics.